2013
DOI: 10.4283/jmag.2013.18.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper Substitution on Structural and Magnetic Properties of NiZn Ferrite Nanopowders

Abstract: In this study, nickel-zinc ferrite nanoparticles, with the chemical formula of Ni 0.3 Zn 0.7-x Cu x Fe 2 O 4 (where x = 0.1-0.6 by step 0.1), were fabricated by the sol-gel method. The effect of copper substitution on the phase formation and crystal structure of the sample was investigated by X-ray diffraction (XRD), thermo-gravimetry (TG), differential thermal analysis (DTA), Fourier transform infrared spectrometry (FT-IR), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is well known that NiZn-ferrite is a material with a combination of normal and inverse spinel structure, in which oxygen ions form face-centered cubic (fcc) close-packed lattice while Zn 2þ ions tend to occupy the tetrahedral interstices (A sites), Ni 2þ ions preferentially occupy the octahedral interstices (B sites), and Fe 3þ ions occupy both the A and B site [14,15]. The soft magnetic properties of ferrites are determined by the type of the cations and their distribution in the A and B sites, and it has been reported that the cation distribution is different in some nanostructure ferrite compared to their bulk counterparts [16,17]. Similarly, the unordered cation distribution and large amount of defects in nanostructure NiZn-ferrite thin films will lead to a disordered spinel structure, thus resulting in the change of magnetic properties such as saturation magnetization M s and coercivity H c compared to bulk NiZn-ferrite.…”
Section: Introductionmentioning
confidence: 98%
“…It is well known that NiZn-ferrite is a material with a combination of normal and inverse spinel structure, in which oxygen ions form face-centered cubic (fcc) close-packed lattice while Zn 2þ ions tend to occupy the tetrahedral interstices (A sites), Ni 2þ ions preferentially occupy the octahedral interstices (B sites), and Fe 3þ ions occupy both the A and B site [14,15]. The soft magnetic properties of ferrites are determined by the type of the cations and their distribution in the A and B sites, and it has been reported that the cation distribution is different in some nanostructure ferrite compared to their bulk counterparts [16,17]. Similarly, the unordered cation distribution and large amount of defects in nanostructure NiZn-ferrite thin films will lead to a disordered spinel structure, thus resulting in the change of magnetic properties such as saturation magnetization M s and coercivity H c compared to bulk NiZn-ferrite.…”
Section: Introductionmentioning
confidence: 98%
“…In terms of spinel compounds, this substance has attracted a lot of attention because its properties are suitable for various applications, such as optical coating or host matrix [5,6], high-temperature ceramic materials [7,8], electronic devices [9,10], magnetic materials [11,12], pigments [13,14], and photocatalysis [15,16]. In principle, the applications of these spinel compounds are governed by peculiar properties that depend on the chemical composition and microstructure of the compound.…”
Section: Introductionmentioning
confidence: 99%